TINDAK PIDANA DAN PENEGAKAN HUKUM LINGKUNGAN HIDUP DAN KEHUTANAN (2021-2023) PADA SEKSI WILAYAH I MANOKWARI - Pulunggono, Jokopulunggono; Wahyudi; Mahmud (Fakultas Kehutanan Universitas Winaya Mukti, 2024)
Environmental and forestry crimes (LHK) include various typologies such as illegal logging, forest and land burning, environmental pollution, environmental damage, forest encroachment, wild plants and animals. These criminal acts are committed by individuals and corporations (companies). This article discusses a summary of the results of law enforcement against LHK criminal acts in the Manokwari Region I Section of the LHK Security and Law Enforcement Center for the Maluku and Papua Regions. This research was carried out by analyzing documents from various sources regarding LHK criminal acts, statutory regulations and interviews over a period of 3 (three) years, namely 2021-2023. The results of the research show that Civil Servant Investigators (PPNS) Section I Manokwari have handled 16 (sixteen) LHK crimes. Criminal acts tend to decrease from 2021 (47%), 2022 (33%), 2023 (20%) and most often occur in Sorong City (56%). The most dominant criminal act is illegal logging (37%) and the regulation that is frequently used is Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction, namely 9 (nine) cases or 56%. Most of the perpetrators were carried out by individuals, 81%, while only 19% were corporations. There are still many crimes in the forestry sector, namely 87%, and environmental crimes at 13%. Of all criminal acts followed up by law enforcement through investigations by Civil Servant Investigators (PPNS) Section 1 Manokwari, 81% were declared complete by the public prosecutor and 75% had received decisions from the court.